Eugene O’Neill’s Protest about White Supremacy in All God’s Chillun Got Wings - Setyani Setyani; Bernadus Hidayat (Universitas Gadjah Mada, 2019)
This article investigates Eugene O’Neill’s protest against racism and white supremacy found in his play, All God’s Chillun Got Wings. O’Neill expressed his protest in relation to white supremacy as a reflection of some part of his life. Therefore, M.H. Abrams’ (1971) expressive approach is applied. To answer the research questions, the primary data of this research, i.e., excerpts from All God’s Chillun Got Wings script and Eugene O’Neill biography related to white supremacy were collected and analyzed. Dictionaries, newspapers, journals, and articles related to the play and Eugene O’Neill were used as secondary data to support the analysis. The analysis reveals that O’Neill criticizes the different treatments because of skin colour and how to fix it. The study suggests that the different treatments related to the racial differences did not only affect the oppressed but also the oppressor. The solution Eugene O’Neill presented to remedy the situation is to see each other in the same standing regardless of the difference in racial genetics.